Contractor Selection Using Fuzzy Hybrid AHP-VIKOR - S. Zamani; H. Farughi; M. Soolaki (International Journal of Research in Industrial Engineering, 2013)
In recent years, contractors play a major role in construction projects of buildings, roads, or waterworks under supervision of project owners or employers of these projects. So, that is why contractor selection is an important decision for employers. Contractor selection is a multicriterion decision problem and resolving the problem of evaluation and although ranking the candidate contractors has become a key factor for firms and enterprises. In this article, the proposed a new hybrid AHP and VIKOR methodology is applied to select the best contractor. Because of dealing with uncertain values for the criteria, fuzzy logic is used to solve this problem and the evaluation data for the alternatives have been expressed in linguistic terms. So, both AHP and VIKOR methods are performed under fuzzy environment. The fuzzy AHP is applied to form the structure of the contractor selection problem and also to obtain weights of the evaluation criteria, and fuzzy VIKOR method is used to determine final ranking. A numerical example is proposed to illustrate an application of the proposed method that demonstrates the effectiveness of the proposed model.